THE GUEST’S PREFERENCES OF THREE-STAR HOTEL ROOMS BASED ON VISUAL AND PHYSICAL PERCEPTION - Nadya Nilafianty Prasetya; Maria Immaculata Ririk Winandari (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2019)
ABSTRACT The development of the tourism industry in Indonesia needs to be supported by appropriate facilities and infrastructure. Hotel as one of the supporting tourism in Indonesia has to be properly expanded. According to the data from Central Bureau of Statistics (BPS), the occupancy rate of star-rated hotels continues to increase over time. One of the factors affecting the customer's decision in choosing a hotel is its interior design. Interior elements consist of floor, wall, ceiling, and furniture. The wall element is one of the interior elements that are attractive to visitors. To find out the perception of hotel visitors, the author surveyed five three-star hotels in Jakarta. The five hotels are Maxone hotel in Matraman, Yellow Hotel in Harmoni, Lynt Hotel in Gambir, Park 5 Hotel and Swissbellinn both are located in Simatupang. The method used in this study is a mixed-method with a visual perception approach in the form of direct interviews and distributed questionnaires to 40 respondents. The results of the research show that several wall criteria of the hotel that are suitable for visitors among others are: bright wall colors and walls with soothing color schemes. Keywords: Guest’s preferences, hotel rooms, visual perception, wall design